Controlling semiconductor nanowire light emission by a photonic crystal cavity : towards integrated nanolasers - Wilhelm, Christophe (2015)
Miniature, low-consumption and efficient light sources are of major importance for the spreading of optical technologies. In particular, photonic circuits are investigated in view of reducing the energy consumption of on-chip interconnects. Semiconductor nanowires have emerged recently as a new kind of active media, suitable for use as photodetectors and emitters, owing to their unique physical properties. Yet, an optical cavity is critical to take full advantage of nanowires in the frame of light emission. Photonic crystal membranes are good candidates as they are very flexible and provide a large degree of control over the confinement of light. This thesis is about the study of structures integrating nanowires with photonic crystals for achieving control over their emission properties. Two possibilities have been investigated during the course of my work. First, the geometry consisting of a wire placed vertically on top of a two dimensional photonic crystal cavity was considered. This approach potentially allows for high degrees of integration as wires are directly grown on top of the cavity. I have theoretically demonstrated that the optical feedback from the cavity is enough to trigger lasing. The second architecture studied in this work consists of an embedded nanowire into a Silicon Nitride photonic crystal waveguide. A self-cavity is generated by the wire presence, achieving a theoretical Q-factor exceeding 104, which is enough to provide suitable feedback to the emitter. Our modeling results and first experimental demonstrations of semiconductor nanowires embedded in photonic crystal cavities clearly demonstrate the advantages of this approach to control the light emission properties of nanowires, and the potential for large-scale integration of virtually any light-emitting nanowire material.